Enhancement of Freeze and Spray Drying Techniques for the Preservation of Aspergillus Niger Spores - Ahmad, Mohd Azman (2009)
In this study, Aspergillus niger spores were powderised using freeze and spray drying techniques prior to the treatment of palm kernel cake (PKC) for subsequently used as an animal feed particularly for poultry. Initially, effects of several harvesting agents on the recovery of the spores from the growth solid media were investigated. Prior to freeze and spray drying processes, several cryoprotective agents (skimmed milk, maltose, glucose, lactose and leucine) were added to the prepared spore suspension in order to maintain high cell viability. In the freeze drying process, cell viability was reduced from 1.2 x 1012 CFU/g to 2.7 x 1010 CFU/g when using 10% w/v of glucose as the cryoprotective agent and achieved about 1.65 of log reduction. Meanwhile, highest cell viability (1.8 x 1011 CFU/g) was exhibited using 10% w/v of maltose compared to 10% w/v of skimmed milk (2.7 x 1010 CFU/g), which examined immediately after freeze drying process. However, 10% w/v skimmed milk showed the best cryorptective agent for long storage life. The viable cells were survived up to 61 weeks of storage using 10% w/v skimmed milk, while it was only 49 weeks for both 10% w/v glucose and 10% w/v maltose In the spray drying process, the cell viability reduced from 6.0 x 1012 CFU/g to 6.1 x 1010 CFU/g when using skimmed milk as the protective agent. The combination of 10% w/v lactose and 10% w/w leucine as the protective agents prior to spray drying process showed drastically decreased of cell viability from 5.0 x 1012 CFU/g to 4.3 x 1010 CFU/g. However, increased of leucine percentage (12% w/w leucine) in the combination of the cryoprotective agents slightly improved the cell viability from 4.3 x 1010 CFU/g to 6.0 x 1010 CFU/g. Comparison between freeze drying and spray drying process in terms of drying methods, cell viability immediately after drying process, survival rate, and long term storage product was made. As a result, the freeze drying process using combination of selected cryoprotective agents was showed to be the preferred method for long storage life. Generally, freeze drying process exhibited highest cell viability, high survival rate of spores and long term storage stability of product. Meanwhile, spray drying process showed shorter storage life of viable cells, which only last up to week 29 as compared to week 61 for freeze drying process and there were no viable cells detected at the end of each storage life. Higher reducing sugars were obtained from both spray dried (141.10 mg/g PKC) and freeze dried (86.83 mg/g PKC) A. niger spores compared to fresh A. niger spores that produce 58.57 mg/g PKC. While for mannanase production for spray dried spores was 341.75 U/g of PKC, freeze dried was 330.25 U/g of PKC and fresh A. niger 346.75 U/g of PKC. Powderised spores have shown promising results to reduced NDF, ADF, and CF in PKC and increase CP.